Document File Security Using The Rsa Algorithm - Yusuf Ramadhan Nasution; Suhardi Suhardi; Rahmadani Nasution (CV. AFDIFAL MAJU BERKAH, 2026)
The rapid development of digital technology has increased the need for secure document storage and transmission, especially for confidential information. This study aims to develop a web-based document security application using the RSA (Rivest–Shamir–Adleman) algorithm to protect document contents from unauthorized access. The research method used is Research and Development (R&D) with the Software Development Life Cycle (SDLC) Waterfall model, consisting of planning, analysis, design, implementation, and testing stages. The application was developed using PHP and implemented to secure DOCX, PDF, and XLSX document formats with a maximum file size of 2 MB. The RSA algorithm was applied through encryption using a public key and decryption using a private key. System testing was performed using Black-box Testing and Avalanche Effect analysis to evaluate application performance. The results show that the application successfully encrypts and decrypts document files while maintaining the original document contents after the decryption process. The Avalanche Effect testing obtained an average value of 49.99%, indicating that the RSA algorithm provides adequate security in protecting document contents. Therefore, the developed application can be used as an alternative solution for securing confidential digital documents.